Influência da temperatura sobre a longevidade, fecundidade e atividade hematofágica de Aedes (Stegomyia) albopictus Skuse, 1894 (Diptera, Culicidae) sob condições de laboratório - Calado,Daniéla C. (2002)
Influence of temperature on longevity, fecundity, and haematophagic activity of Aedes (Stegomyia) albopictus Skuse, 1894 (Diptera, Culicidae) under laboratory condition. Based on adults of Aedes albopictus maintained under four constant temperatures, 15ºC, 20ºC, 25ºC and 30ºC, longevity of males and females, fecundity, eggs viability, number of days from emergence to the first bloodsucking, and duration of the preoviposition period were observed. The average of the longevity for female was 19.45, 59.35, 61.55 and 42.72 days, under 15ºC, 20ºC, 25ºC and 30ºC, respectively. The greatest average number of bloodsucking per female was 8.32, under 25ºC. The average number of eggs per female was 1.00, 73.91, 269.87 and 183.69, and the greatest rates of viable eggs per female was 25ºC and 30ºC. The haematophagic activities and the oviposition were significantly influenced by temperature.